Heterochromatin structure: Lessons from the budding yeast. Issue 10 (30th October 2014) - Bi, Xin
Abstract The eukaryotic genome can be roughly divided into euchromatin and heterochromatin domains that are structurally and functionally distinct. Heterochromatin is characterized by its high compactness and its inhibitory effect on DNA transactions such as gene expression. Formation of heterochromatin involves special histone modifications and the recruitment and spread of silencing complexes and causes changes in the primary and higher order structures of chromatin. The past two decades have seen dramatic advances in dissecting the molecular aspects of heterochromatin because of the identification of the histone code for heterochromatin as well as its writers and erasers (histone‐modifying enzymes) and readers (silencing factors recognizing histone modifications). How heterochromatic histone modifications and silencing factors contribute to the special primary and higher order structures of heterochromatin has begun to be understood. The budding yeast Saccharomyces cerevisiae has long been used as a model organism for heterochromatin studies. Results from these studies have contributed significantly to the elucidation of the general principles governing the formation, maintenance, and function of heterochromatin. This review is focused on investigations into the structural aspects of heterochromatin in S. cerevisiae. Current understanding of other aspects of heterochromatin including how it promotes gene silencing and its epigenetic inheritance is briefly summarized. © 2014 IUBMB Life, 66(10):657–666, 2014